The Role of Prior Language in The Acquisition of English Language by Indonesian Adult - Andina Cipta Wardani; Catur Kepirianto (UNIB Press, 2023)
Many factors influence the second language acquisition process for adulthood. One of the factors is the prior language (L1) that a person possesses. This research analyses the role of prior language in adults who are claimed hardly to acquire a second language (L2). This research also tried to figure out how the L1 affects the L2. This research is supposed to know whether L1 prevents adults from acquiring a second language or, instead, L1 helps adults acquire a second language (L2). It is descriptive qualitative research. The instruments are questionnaires via Google form and voice records to be analysed with the Speech Analyzer application. The population is employees who work in the branch office of a construction company with a total of about 100 employees. Their L1 is Indonesian, and their L2 is English. The sampling method used is a random sampling from various company divisions that communicate with foreign co-workers or clients and deal with documents written in English. This research shows that prior language determines adults’ accents and pronunciation, interpreting the meaning, processing the information in L1 then producing it in L2. Significantly, the prior language does help adults acquire English as a second language.